Correction: Plasmonic Au nanoclusters dispersed in nitrogen-doped graphene as a robust photocatalyst for light-to-hydrogen conversion. Issue 41 (18th October 2021) - Van Dao, Dung; Cipriano, Luis A.; Di Liberto, Giovanni; Nguyen, Thuy T. D.; Ki, Sang-Woo; Son, Hoki; Kim, Gyu-Cheol; Lee, Kang Hyun; Yang, Jin-Kyu; Yu, Yeon-Tae; Pacchioni, Gianfranco; Lee, In-Hwan
Abstract : Correction for 'Plasmonic Au nanoclusters dispersed in nitrogen-doped graphene as a robust photocatalyst for light-to-hydrogen conversion' by Dung Van Dao et al., J. Mater. Chem. A, 2021, DOI: ; 10.1039/D1TA05445G .